Idiopathic Non Cirrhotic Portal Hypertension and Spleno-Portal Axis Abnormalities in Patients with Severe Primary Antibody Deficiencies. (31st March 2014) - Pulvirenti, Federica; Pentassuglio, Ilaria; Milito, Cinzia; Valente, Michele; De Santis, Adriano; Conti, Valentina; d'Amati, Giulia; Riggio, Oliviero; Quinti, Isabella
Abstract : Background and Aim . Portal hypertension has been reported in association with acquired and primary immune deficiencies without a comprehensive description of associated spleno-portal axis abnormalities. Pathological mechanisms are poorly defined. Methods . Observational, single centre study with the aim of assessing the prevalence of spleno-portal axis abnormalities in an unselected cohort of 123 patients with primary antibody deficiencies and without known causes of liver diseases regularly followed up for a mean time of 18 ± 14 years. A cumulative period of 1867 patients-year was analysed. Clinical and immunological data, abdominal ultrasounds, CT scans, and endoscopy features were included in the analysis. Results . Twenty-five percent of patients with primary antibody deficiencies had signs of portal vein enlargement but only 4% of them had portal hypertension, with portal systemic collaterals. Liver biopsies showed liver sinusoids congestive dilatation, endothelization, and micronodularity fulfilling the criteria for noncirrhotic portal hypertension. Patients with portal vein enlargement had severe clinical and immunological phenotypes. Conclusions . In primary antibody deficient patients, infections, inflammations, splenomegaly, increased blood venous flow, and lymphocyte abnormalities contribute to establishment of liver damage possibly leading to noncirrhotic portal hypertension. Patients with primary antibody deficiency should be considered a good model to give insight into the pathological mechanisms underlying noncirrhotic portal hypertension.